Economic analysis of Electrical Muscle Stimulator with Multipath technology for the treatment of stress urinary incontinence: a UK-based cost-utility analysis. (1st September 2020) - Javanbakht, Mehdi; Mashayekhi, Atefeh; Monga, Ash; Atkinson, Jowan; Branagan-Harris, Michael
Abstract: Background: Stress urinary incontinence (SUI) is a debilitating and highly prevalent condition in the UK. The condition is associated with a significant economic burden for affected patients and society. Current treatment options for SUI include minimally invasive therapies, medication and surgical intervention for the most serious cases. Electrical Muscle Stimulator with Multipath technology is a recently developed device for the treatment of SUI that relies on neuromuscular external electrical stimulation (NEES) technology. The clinical efficacy of the device has been proven in previous studies, but existing evidence surrounding its economic viability is limited. Objectives: To assess the cost-utility of the Electrical Muscle Stimulator with Multipath technology Therapy device for the treatment of SUI amongst women in a UK setting. Methods: An economic model was developed to consider the cost-utility (cost per quality-adjusted life-year [QALY] gained) of Electrical Muscle Stimulator with Multipath technology compared with current practice. A Markov model was developed, with costs and health effects estimated over the lifetime of the patient in the base-case analysis. The model was developed to reflect the treatment pathways typically followed by patients with SUI in the UK. Parameter uncertainty was explored in deterministic and probabilistic sensitivity analyses. Results: Base-case results indicate that Electrical Muscle Stimulator with Multipath technology results in cost savings and QALY gains over the patient's lifetime. In the "cure" analysis, the intervention is £250 less costly and leads to a 0.03 QALY gain per patient, while in the "improvement analysis", the intervention is £327 less costly and leads to a 0.13 QALY gain per patient. Results from the probabilistic sensitivity analyses show that the likelihood of Electrical Muscle Stimulator with Multipath technology being cost-effective is greater than 74% across all willingness-to-pay thresholds in the two analyses presented. Conclusions: Electrical Muscle Stimulator with Multipath technology is a potentially cost-effective treatment option for patients with SUI who have failed first-line treatment. It could reduce costs to the health care service and improve quality-of-life for selected patients over their lifetime.